Prediction of Production Using the Fuzzy Mamdani Inference Method - Sunjana, Miss (International Journal of Advanced Science and Technology, 2019)
The problem often faced by companies in production activities is determining the number of products that must be produced. In this paper we discuss the prediction of the production of a product based on the number of requests and the amount of inventory of the product. The method used in solving these production problems is the mamdani fuzzy inference method. The mamdani fuzzy inference method was originally introduced by Ebrahim Mamdani in 1975. This method has four stages, namely, the formation of fuzzy sets, application of function implications, composition of rules, and affirmation or defuzzyfication. This method is quite good in determining the amount of production of a product based on the number of requests and the amount of inventory.